Nanocomposites SnO(2)/SiO(2) for CO Gas Sensors: Microstructure and Reactivity in the Interaction with the Gas Phase - Gulevich, Dayana (Materials (Basel), 2019)
Nanocomposites SnO(2)/SiO(2) with a silicon content of [Si]/([Sn] + [Si]) = 3/86 mol.% were obtained by the hydrothermal method. The composition and microstructure of the samples were characterized by EDX, XRD, HRTEM and single-point Brunauer-Emmet-Teller (BET) methods. The surface sites were investigated using thermal analysis, FTIR and XPS. It is shown that the insertion of silicon dioxide up to the value of [Si]/([Sn] + [Si]) = 19 mol.% stabilizes the growth of SnO(2) nanoparticles during high-temperature annealing, which makes it possible to obtain sensor materials operating stably at different temperature conditions. The sensor properties of SnO(2) and SnO(2)/SiO(2) nanocomposites were studied by in situ conductivity measurements in the presence of 10–200 ppm CO in dry and humid air in the temperature range of 150–400 °C. It was found that SnO(2)/SiO(2) nanocomposites are more sensitive to CO in humid air as compared to pure SnO(2), and the sample with silicon content [Si]/([Sn] + [Si]) = 13 mol.% is resistant to changes in relative air humidity (RH = 4%–65%) in the whole temperature range, which makes it a promising sensor material for detecting CO in real conditions. The results are discussed in terms of the changes in the composition of surface-active groups, which alters the reactivity of the obtained materials.